2016
DOI: 10.18632/oncotarget.7430
|View full text |Cite
|
Sign up to set email alerts
|

The lectin-like oxidized LDL receptor-1: a new potential molecular target in colorectal cancer

Abstract: The identification of new biomarkers and targets for tailored therapy in human colorectal cancer (CRC) onset and progression is an interesting challenge.CRC tissue produces an excess of ox-LDL, suggesting a close correlation between lipid dysfunction and malignant transformation. Lectin-like oxidized LDL receptor-1 (LOX-1) is involved in several mechanisms closely linked to tumorigenesis.Here we report a tumor specific LOX-1 overexpression in human colon cancers: LOX-1 results strongly increased in the 72% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 41 publications
(52 reference statements)
1
45
0
Order By: Relevance
“…Given the pivotal role of cancer cells migration and invasion in cancer progress, we performed transwell assay to evaluate the effect of LOX-1 on the migratory and invasive potential of GC cells in vitro . We found that LOX-1 promotes GC cells migration and invasion, which is consistent with previous studies conducted in other types of cancer cells91128. It has been known that EMT plays important role in the invasive and metastatic processes of cancer cells29.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Given the pivotal role of cancer cells migration and invasion in cancer progress, we performed transwell assay to evaluate the effect of LOX-1 on the migratory and invasive potential of GC cells in vitro . We found that LOX-1 promotes GC cells migration and invasion, which is consistent with previous studies conducted in other types of cancer cells91128. It has been known that EMT plays important role in the invasive and metastatic processes of cancer cells29.…”
Section: Discussionsupporting
confidence: 92%
“…Activation of LOX-1 promotes transformation, motility and growth of several cancer cells, while down-regulation of LOX-1 can prevent such processes9. Moreover, some studies have shown that LOX-1 overexpression is a significant prognosis of tumor progression in advanced-stage prostate cancer10, colorectal cancer11 and squamous non-small cell lung cancer12.…”
mentioning
confidence: 99%
“…The shifting of acetylation pattern suggests a possible involvement of LOX-1 in epigenetic modulation of transcription of tumor suppressor genes [176]. …”
Section: Lox-1 Signaling and Role In Atherogenesis And Tumorigenesismentioning
confidence: 99%
“…Several lipid metabolic genes, including orl1, are consistently overexpressed in diverse cancer cell lineages and, importantly, the expression of these genes is critical to cellular transformation, as well as in maintaining the transformed state. A meta-analysis of gene expression profiles of 950 cancer cell lines stored in the Gene Expression Atlas at the EMBL-EBI database (http://www.ebi.ac.uk/gxa/ gene/ENSG00000173391#) reveals that the LOX-1 gene is up-regulated in 57% of bladder and cervix cancer cells, 11% of mammary gland cancer cells, 10% of lung cancer cells, and in 20% of colon rectal cancer (CRC) cells [24,26,47]. The expression of LOX-1 is modulated since the early stage of tumor development, suggesting a potential role in the insurgence and progression of the disease and associated with more aggressive and metastatic stage tumors.…”
Section: S Raniolo Et Al / Cholesterol Level Regulates Lectin-like mentioning
confidence: 99%
“…As in atherosclerosis, the ox-LDL-LOX-1 interaction activates the inflammatory pathway through NF-κB activation [39] increases the expression of proatherogenic molecules such as VEGF, MMP-2 and MMP-9 and, in cancer cells stimulates proliferation [24]. Depletion of LOX-1 receptors protects against tumorigenicity, motility and growth of these cells [26,47].…”
Section: S Raniolo Et Al / Cholesterol Level Regulates Lectin-like mentioning
confidence: 99%